Psychosocial and psychological interventions' effectiveness among nurses in intensive care units caring for pediatric patients: A systematic review and meta-analysis - Choi, Mi Hyang; Lee, Misoon (Frontiers in Pediatrics, 2022)
Objective: This review aimed to evaluate the effectiveness of psychosocial and psychological interventions in nurses among intensive care units caring for pediatric patients. Methods: A literature search was performed in PubMed, EMBASE, CINAHL databases, using preferred reporting items for systematic reviews and meta-analysis guidelines. Study design, population characteristics, contents of the programs, measured outcomes, and results were systematically reviewed from 8 selected studies. To estimate the effect size, a meta-analysis of the studies was performed using the RevMan 5.3 program. The effect size used was the standardized mean difference. Results: Of 1,630 studies identified, 4 met the inclusion criteria, and 3 studies were used to estimate the effect size of psychosocial and psychological interventions. The primary outcome variable of these studies was stress. The effect of the intervention program on stress was also found to have no effect in individual studies, and the overall effect size was not statistically significant (standardized mean difference = -0.06; 95% confidence interval: -0.33, 0.20; Z = 0.48, p = 0.630). However, according to the individual literature included in this study, after the stress management program was applied as a group, a significant stress reduction was shown in the experimental group (p = 0.021). Conclusions: These results show that psychosocial and psychological interventions were effective in stress management by a group approach. Therefore, it is necessary to develop psychosocial support interventions for stress management of nurses among intensive care units caring for pediatric patients more diversely.